EDUCATIONAL REFORM AND THE ENGLISH SCHOOLS OF QUÉBEC - Freeland, Elaine (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1999)
ABSTRACT. Since the last educational reform in Québec at the beginning of the 1980s the face of English Québec has changed, as has its attitude towards govemment policies in education. In 1999, the newly formed English language school boards are joining forces to share resources and expertise and to take charge of implementation in their schools. RÉSUMÉ. Depuis la dernière réforme de l’éducation au Québec au début des années 1980, le visage du Québec anglophone a radicalement changé, tout comme son attitude à l’égard des politiques gouvernementales sur l’éducation. En 1999, les commissions scolaires anglophones de création récente ont décidé d’unir leurs forces pour échanger des ressources et des expertises et prendre en charge la mise en oeuvre des réformes dans leurs écoles.